Mixed silage with Chinese cabbage waste enhances antioxidant ability by increasing ascorbate and aldarate metabolism through rumen Prevotellaceae UCG-004 in Hu sheep - Li, Chuang; Chen, Ning; Zhang, Xingxing; Shahzad, Khuram; Qi, Ruxin; Zhang, Zhenbin; Lu, Zhiqi; Lu, Yue; Yu, Xiang; Zafar, Muhammad Hammad; Wang, Mengzhi; Liu, Wujun (Frontiers in Microbiology, 2022)
Silage is rich in nutrients, which can make up for the lack of seasonal roughage, and has a certain promotion effect on the intensive feeding of ruminants. In addition, silage can maintain the rumen function of ruminants to a certain extent and reduce the risk of rumen acidosis and abomasum translocation. The purpose of this study is to investigate the effects of the mixed silage of Chinese cabbage waste and rice straw (mixed silage) on antioxidant performance, rumen microbial population, and fermentation metabolism of Hu sheep. 16 healthy Hu sheep (39.11 ± 1.16 kg, 5.5 months) were randomly divided into two groups (the control group and the mixed silage group) with 8 animals in each group. The control group was fed with farm roughage (peanut seedlings, corn husk and high grain shell) as forage, and the mixed silage group was fed with the mixed silage as forage. The results showed that The mixed silage had no effect on the growth performance of Hu sheep (P > 0.05). Ruminal butyric acid, total volatile fatty acids (TVFA), and ammonia nitrogen (NH3-N) concentration in the mixed silage group were increased, whereas the pH was decreased (P < 0.05). The blood and rumen total antioxidants capacity (T-AOC) concentration in the mixed silage group was higher, and the malondialdehyde (MDA) content in rumen, serum, liver and kidney was lower than that in the control group (P < 0.05). Illumina sequencing results showed that PCoA and ANOSIM results indicated that the mixed silage affected the bacterial composition of the rumen microbes. The mixed silage increased the proportion of Prevotellaceae UCG-004, and there was a positive correlation with Vitamin C (Vc) in mixed silage. In addition, PICRUSt functional prediction analysis showed that ascorbate and aldarate metabolism were up-regulated in the mixed silage group (P < 0.05). In conclusion, higher contents of VC and neutral detergent fiber (NDF) in the mixed silage were beneficial to the growth and reproduction of Prevotellaceae UCG-004, and the butyric acid produced by Prevotellaceae UCG-004 significantly up-regulated the metabolism of ascorbate and aldarate metabolism, thereby improving the antioxidant properties of Hu sheep.